2013
DOI: 10.1002/art.37854
|View full text |Cite
|
Sign up to set email alerts
|

Deletion Variants of RABGAP1L, 10q21.3, and C4 Are Associated With the Risk of Systemic Lupus Erythematosus in Korean Women

Abstract: Objective. Several copy number variations (CNVs) have been found to be associated with systemic lupus erythematosus (SLE) through the target gene approach. However, genome-wide features of CNVs and their role in the risk of SLE remain unknown. The aim of this study was to identify SLE-associated CNVs in Korean women.Methods. Genome-wide assessments of CNVs were performed in 382 SLE patients and 191 control subjects, using an Illumina HumanHap610 BeadChip genotyping platform. SLE-associated CNV regions that wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 26 publications
4
32
0
Order By: Relevance
“…As a physician, this is important to keep in mind when using C4 levels to monitor disease activity 24. Low gene copy numbers of the C4A gene increase the risk of SLE in a Korean population, whereas increased gene copy numbers are protective 27. On the other hand, copy numbers of the C4B gene are not associated with SLE 28.…”
Section: Genetic Associationsmentioning
confidence: 99%
“…As a physician, this is important to keep in mind when using C4 levels to monitor disease activity 24. Low gene copy numbers of the C4A gene increase the risk of SLE in a Korean population, whereas increased gene copy numbers are protective 27. On the other hand, copy numbers of the C4B gene are not associated with SLE 28.…”
Section: Genetic Associationsmentioning
confidence: 99%
“…15 28 29 Low gene copy number (GCN) for total C4 or C4A deficiency has been observed as a risk factor of human systemic lupus erythematosus. [30][31][32][33] Many earlier epidemiological studies of complement C4A and C4B in rheumatic diseases, including JDM, were based on an incomplete or inaccurate model with two-locus (C4A-C4B) on a haplotype for data interpretation, and thus the conclusions drawn became uncertain. [34][35][36][37] Here we perform an investigation of C4 genetic diversity and examine the effects on the risk and pathogenesis of JDM, with further considerations to the presence and absence of HLA-DRB1 risk and protective alleles.…”
Section: Introductionmentioning
confidence: 99%
“…CNVs account for a major proportion of human genetic variation, and several reports have suggested that CNVs play a role in susceptibility to diseases, especially autoimmune diseases (19)(20)(21)(22)(23). However, no GWAS exploring ASassociated CNVs have been reported.…”
mentioning
confidence: 99%